Fábrica Campos de Melo: projecto de reabilitação - Vicente, Sérgio Paulo Gomes (2014)
Submitted by Joana Lopes Dias (jdias@ubi.pt) on 2014-09-04T09:42:11Z No. of bitstreams: 15 0 Memória Descritiva e Justificativa.pdf: 269445 bytes, checksum: 9a20ea58eb6f220b3de94051334cb617 (MD5) 1.1planta de localização.pdf: 1689688 bytes, checksum: 813f88defb11d4f8ee36af582802c982 (MD5) 1.2 planta de alteração_demolição.pdf: 273215 bytes, checksum: a7dbc2457164d580245a392e17cc4dc0 (MD5) 1.3 planta da intervenção urbana.pdf: 2036326 bytes, checksum: 4b88aa7abb22ff014bbaf58d70878fee (MD5) 1.4 secções da proposta.pdf: 254313 bytes, checksum: 9f63c01c073113bcddc23312c2173d11 (MD5) 1.5 pormenores construtivos.pdf: 186111 bytes, checksum: 8b44a96d35e7b4b72f98a4dff87d9149 (MD5) 2.1planta de alteração piso 0 e piso 1.pdf: 186958 bytes, checksum: ebd9c7f762a26e9ba5eca53d19daddb4 (MD5) 2.2 planta de alteração do piso 2 e cobertura.pdf: 162298 bytes, checksum: 08893f6c87f5edf5406de149a32a11c6 (MD5) 2.3 alteração alçados.pdf: 179916 bytes, checksum: fe2b4bfb623cbbd96f6b1a02e6ca4574 (MD5) 2.4 planta do piso 0 e piso 1.pdf: 233123 bytes, checksum: 651dba66858f8ed864f6f26eec91a55e (MD5) 2.5 planta do piso 2 e cobertura.pdf: 198129 bytes, checksum: bdedfceba4612b2903613a96344230b8 (MD5) 2.6 cortes.pdf: 196609 bytes, checksum: 553f28bfa06f2a864b18ec611f648a8a (MD5) 2.7 alçados.pdf: 163192 bytes, checksum: 0c3c3c53045682c8ee7a524655c28e28 (MD5) 2.8 corte de fachada.pdf: 347926 bytes, checksum: 5a121dac22f153d42da298056b14348f (MD5) ÍNDICE capa.pdf: 19452 bytes, checksum: 0fc0cdb105e041bed77c4fc94543d3c1 (MD5)